Strategi Bauran Pemasaran Dan Pengaruhnya Terhadap Keputusan Konsumen - Musran Munizu (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2012)
The purpose of this research is to investigate the effect of marketing mix strategy which consist of product, price, place, and promotion on customer decision of PT. Semen Bosowa in Makassar, and to analyze the dominant factor which influence customer decision of PT. Semen Bosowa in Makassar. Population in this research were the customers of cement product of Bosowa in Makassar. The amount of sample were 100 persons. The respondents were chosen by purposive random sampling from the population. Method of analyses which use in this research were both descriptive analysis and Multiple Regression Analysis. Processing data performed by SPSS 18.00. The result shows that marketing mix strategy which consists of product, price, place, and promotion have significant and positive effect on customer decision, and (2) Product factor has dominant effect on customer decision (t-value = 6,517).